Socio-Cultural Characteristics Found in Russian-Korean Translation of Metaphoric Expressions - Lee, Hye-Seung (Meta, 2006)
AbstractTranslation is an act of communication across dissimilar cultures as well as a dynamic activity in which translators are required to make choices and decisions for the purpose of resolving problems. This paper draws on metaphoric expressions and their translations to recapitulate that the work of translation is not limited to the languages or the texts involved but is a dynamic activity that bridges two diverse cultures. Metaphoric expressions are non-literal, have implied meanings, and are used to emphasize a point or to enhance the expression’s impressibility. Furthermore, metaphoric expressions are affected greatly by the culture to which they belong because they are created through a complex interaction between object, image, and sense. Consequently, in order to properly communicate the true meanings of these metaphoric expressions, translators play the role of an active mediator by either replacing the metaphoric expression found in ST with a different but compatible metaphoric expression or by using non-metaphoric, descriptive expressions or by appending additional explanation. This paper uses Korean translations of metaphoric expressions found in Russian source texts as examples to discuss the socio-cultural differences between the two cultures, how these characteristics are revealed in Russian-Korean translations, and how these issues are overcome. Based on the research results, the paper also emphasizes that understanding the vastly different socio-cultural characteristics of these two cultures is essential to the field of Russian-Korean translation with its relatively short history, to not only improve the quality of translations but also for the field’s continual advancements.